The Effect of Implementing the Problem Based Learning Model Using Digital Platforms on the Success of Learning Accounting - Kuswanto, Kuswanto; Silaban, Erika Sabatany; Putra, Iwan; Liputo, Muhammad Arif (UIR Press, 2024)
Learning accounting not only requires students to master accounting concepts but also requires mastering skills in managing financial information in an accounting system. Accounting learning requires an effective model that focuses on students who can practice their skills and develop their knowledge, namely the